Rancang Bangun Aplikasi E-Learning Berbasis Mobile Untuk Mengimplementasikan Menu Quiz dengan Metode User Centered Design - Aulia Nugraheni; Sri Wulandari; RR Hajar Puji Sejati; Agus Suhendar (STMIK Budi Darma, 2024)
Nowadays, the development of technology in the world is very rapid. Many of the latest innovations have been created to help humans in carrying out their activities, both in person and virtually. Currently, all services and services are digitized. This digitalization process is also happening in the world of education in Indonesia. As an educational institution at the junior secondary level, SMPN 1 Rembang plays an important role in the development of science. SMPN 1 Rembang must improve the quality of education it provides. Currently, the learning process at SMPN 1 Rembang is still conventional, so it has not been able to maximize the effectiveness and efficiency of the learning system. The teaching and learning process between students and teachers can only be done on condition that there is a meeting between students and teachers in the classroom directly. This research aims to develop an E-Learning system presented in a mobile-based application so that it can be used anywhere and anytime. This system is developed using PHP programming language and MySQL database that applies User Centered Design (UCD) method. This method is used to analyze the needs and design of the system which consists of fonts, layouts, and features. With this system, SMP Negeri 1 Rembang can provide a learning system to each student with a more advanced and modern because this system is able to answer all teaching and learning needs.